Studies in Ancient Technology. Vol. 4. The Fibres and Fabrics of Antiquity. Washing, Bleaching, Fulling and Felting. Dyes and Dyeing. Spinning. Sewing. Basketry and Weaving. Weaving and Looms. Fabrics and Weavers. Second ed. - Forbes, R. J. (1964)
First ed. 1956 = 19:a:12.